2014
DOI: 10.1590/s0036-46652014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial and Cytotoxic Activities of Plant Extracts From Southern Minas Gerais Cerrado

Abstract: The antimicrobial activity of plant hidroethanolic extracts on bacteria Gram positive, Gram negative, yeasts, Mycobacterium tuberculosis H37 and Mycobacterium bovis was evaluated by using the technique of Agar diffusion and microdilution in broth. Among the extracts evaluated by Agar diffusion, the extract of Bidens pilosa leaf presented the most expressive average of haloes of growth inhibition to the microorganisms, followed by the extract of B. pilosa flower, of Eugenia pyriformis' leaf and seed, of Plinia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 26 publications
2
17
0
8
Order By: Relevance
“…The 70% ethanol extract of rhizomes of H. rostrata collected from Areado city, Brazil, displayed the presence of flavonoids and absence of alkaloids, tannin and saponin [30] . Meanwhile, rhizomes of H. rostrata collected from Columbia showed the presence of terpenoids, proteins, phenolic compounds and carbohydrates [3,31] , when percolated with ethanol without defatting.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 70% ethanol extract of rhizomes of H. rostrata collected from Areado city, Brazil, displayed the presence of flavonoids and absence of alkaloids, tannin and saponin [30] . Meanwhile, rhizomes of H. rostrata collected from Columbia showed the presence of terpenoids, proteins, phenolic compounds and carbohydrates [3,31] , when percolated with ethanol without defatting.…”
Section: Resultsmentioning
confidence: 98%
“…The present study is helpful in finding the extract which showed better antibacterial activity. Literature survey revealed the fact that H. rostrata when extracted with 70% w/v ethanol showed no antibacterial activity at a concentration of 10 mg/ml [30] . Chavasco et al reasoned that this could be due to the solvent chosen for extraction such as 70% w/v ethanol, which failed to extract the active constituents responsible for antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Obtidos os valores de CIM e CBM, os extratos vegetais de E. anomala e P. salutare foram avaliados quanto a sua ação antimicrobiana de acordo com os valores de CIM contra os patógenos estudados onde extratos que apresentam CIM<100 µg/mL têm potencial antimicrobiano promissor (bom), CIM entre 100 -500 µg/mL possui atividade inibitória moderada, CIM entre 500 -1.000 µg/mL apresenta atividade inibitória fraca e extratos que apresentaram CIM superior a 1.000 µg/mL são inativos frente aos patógenos (Fabry et al, 1998;Holetz et al, 2002;Dall'Agnol et al, 2003;Tanaka et al, 2005;Chavasco et al, 2014).…”
Section: Atividade Antimicrobianaunclassified
“…2). Chavasco et al (2014), isolated compounds from plant extracts rich in alkaloids have demonstrated antimicrobial activity in several studies (Osborn, 2003). The antimicrobial activity of flavonoids is also established due to their ability to complex with extracellular and soluble proteins and also with the bacterial cell wall.…”
Section: Anthelmintic Activity Of Plumbago Zeylanicamentioning
confidence: 99%